SISTEM PEMANTAUAN JARINGAN PADA PERANGKAT PEMANTAU CUACA OTOMATIS DENGAN METODE RAD BERBASIS APLIKASI WEB - Lutfi Ruhbi Syahdat (Journal of Research and Publication Innovation, 2026)
Weather is an essential element that influences various aspects of human life, including agriculture, transportation, and health. Global climate change demands an advanced and sustainable weather monitoring system to reduce the risks of extreme weather events. This study aims to develop an effective and efficient network monitoring system for web-based automatic weather monitoring devices. The research methodology uses Rapid Application Development (RAD), which emphasizes a short development cycle through the stages of Requirements Planning, User Design, Construction, and Cutover. This method was chosen due to its flexibility in responding to user feedback and changes in environmental conditions. System validation was conducted using Black Box Testing to ensure functionality without considering the internal structure. The developed system includes user interface features for login, registration, and admin/user dashboards. Administrators can manage weather data and locations, while users can view weather data for each district, temperature charts, humidity levels, and wind speed distribution. Black Box Testing results show that all features function as expected. This study successfully produced an effective web application for collecting, storing, and analyzing weather data. The system provides quick access to weather information and simplifies data management. Its implications include improved capability to anticipate weather changes and support data-driven decision-making across various sectors.